Cr(VI) removal from a synthetic solution using a novel carbonaceous material prepared from oily sludge of tank bottom. (June 2019) - Yang, Huifen; Li, Zhaofeng; Fu, Peng; Zhang, Ge
Abstract: A novel carbonaceous material (NCM), prepared by the pyrolyzation of the oily sludge of tank bottom, was proposed to remove Cr(VI) from a synthetic solution for the first time. The effects of initial Cr(VI) concentration, NCM dosage and initial solution pH on Cr(VI) removal and the adsorption kinetics, the adsorption isothem were investigated. The removal mechanism was studied by comparing the surface properties of NCM before and after the Cr(VI) removal. The results showed that NCM can effectively remove Cr(Ⅵ) from the synthetic solution with the increase of solution pH at equilibrium. At the initial Cr(Ⅵ) concentrations of 40, 100, 150 and 250 mg/L and NCM dosages of 1, 3, 6 and 8 g/L with initial solution pH of 2, the removal efficiency of Cr(VI) was 95.5, 96.8, 95.2 and 81.2%, and the solution pH at equilibrium reached 2.3, 3.5, 5.8 and 7.5, respectively. NCM was suitable for Cr(Ⅵ) removal while the initial Cr(VI) concentration was less than 100 mg/L and initial solution pH was lower than 2.5. Most of Cr(VI) was removed by the reduction of Fe 2+ and S 2− in NCM to Cr(III) and with the generation of stable FeCr2 O4 . Some Cr(VI) may be removed by reacting with Fe 2+ and Ca 2+ to produce CaCrO4 and FeCrO4 on the NCM surface. The dissolution of CaAl2 Si2 O8 and CaS in the solution increased the solution pH at equilibrium. NCM has been proved to be a material with dual functions both chemical reduction and adsorption. Graphical abstract: Image 1 Highlights: NCM can effectively remove Cr(Ⅵ) from a synthetic solution and increase solution pH. NCM is a multifunctional material with chemical conversion of Cr(VI) to Cr(III) and adsorption. The CaAl2 Si2 O8 and CaS in NCM dissolved can increase the solution pH at equilibrium. Cr(VI) was mostly removed by generating FeCr2 O4 on NCM surface with help of S 2− and Fe 2+ .